Pelatihan Perencanaan Keuangan Rumah Tangga Sederhana pada PKK Desa Sambirejo, Geger, Madiun - Elana Era Yusdita; Nur Wahyuning Sulistyowati; Isharijadi Isharijadi; Ferdiana Wahyu Lestari; Puji Lestari (Universitas Pendidikan Indonesia Kampus Purwakarta, 2021)
During the Covid-19 pandemic, homemakers have to struggle more in managing household finances because several sectors are affected and tend to create reserve funds in case of bad work and health. This was felt by PKK women in Sambirejo Village, Geger District, Madiun Regency. The UNIPMA accounting education service team provides a way of managing simple finances from an accounting perspective. The materials consist of SMART financial planning principles, identifying needs versus wants tips on saving and emergency funds, and examples of simple manual and excel-based financial planning applications. Most of the participants considered the material interesting and understandable. Still, their confidence decreased when asked about the ability to apply household financial planning independently - this opens up opportunities for similar services in the future and more for question and answer or personal consultations to better suit the target community's needs.